BLUE GREEN ALGAE FROM RICE FIELDS OF KARIMGANJ DISTRICT, ASSAM, NORTH EAST INDIA: Life Sciences-Botany - MOIRANGTHEM THAJAMANBI; JAYASHREE ROUT; NOORUDDIN THAJUDDIN (International Journal of Life Science and Pharma Research, 2022)
Cyanobacteria (blue green algae) are present abundantly in rice fields and are important in maintaining the rice field fertility through nitrogen fixation. An investigation on cyanobacteria (blue green algae) from the rice fields of Son beel and its nearby adjoining areas of Karimganj district, Southern Assam, India was carried out. A total of thirty four strains of filamentous cyanobacteria were isolated and classified according to their morphological characteristics. The cyanobacterial isolates were classified into ten genera, including seven heterocystous and three non heterocystous genera. The genera Nostoc, Calothrix, Anabaena and Cylindrospermum were the dominant heterocystous group while Lyngbya, Oscillatoria and Phormidium form the non-heterocystous group in the district.